Management of sunflower powdery mildew disease by bioagents and fungicides - Venkataramanamma, K; Neelima, S; Yogeeswarudu, B; Kumar, K Ashok; Sukumar, S (Indian Journal of Plant Protection, 2020)
Field experiment was conducted for the management of sunflower powdery mildew disease by using bioagents and chemicals at Regional Agricultural Research Station (RARS), Nandyal, Andhra Pradesh. This experiment was carried out during Rabi season for three years from 2012-15 by using bioagent (Pseudomonas fluorescens), botanical, neem seed kernel extract (NSKE) and fungicides (difenoconazole, propiconazole) with eight treatments. All the treatments were applied for two times at 45 and 60 days after sowing. During these three years, all the treatments recorded significantly low per cent disease index (PDI) and higher yields compared to control. Pooled analysis of data indicated that lowest PDI was observed in propiconazole @ 0.1% (17.8%) followed by difenoconazole @ 0.05% (20.4%), and neem seed kernel extract + difenoconazole @ 0.05% (22.7%), which were non-significant with each other. At the same time highest yield was observed with the treatment propiconazole @ 0.1% (1273 kg/ha), followed by NSKE @ 0.5% + difenoconazole @ 0.05% (1255 kg/ha), and difenoconazole @ 0.05% (1235 kg/ha). NSKE also performed well in reduction of disease. Performance of other treatments such as P. fluorescens IIOR, P. fluorescens Raichur, P. fluorescens Coimbatore was good in reducing the disease over control but less effective compared to chemical treatments. The treatment propiconazole @ 0.1% recorded highest cost benefit ratio by getting highest net returns.